Study on the Effect of Sodium Hydroxide Treatment on Surface Morphology and Tensile Properties of Oil Palm Empty Fruit Bunch - Samsudin, Widad Syamila; Abu Bakar, Hasniza (Recent Trends in Civil Engineering and Built Environment, 2024)
Commercial by-products, such as EFB fibre, might be utilised to make CBFB instead. To determine the viability of adding EFB into Cement Bonded Fibreboard (CBFB), a It is necessary to conduct a compatibility assessment for the physical and mechanical properties of Cement Bonded Fibreboard (CBFB) made of Empty Fruit Bunch (EFB). However, EFB fibre and cement combinations have been reported to have compatibility concerns since the fibres contain residual oil, sugar, lignin, hemicellulose and cellulose that prevent cement setting and hydration. Aside from that, the physical and mechanical properties of CBFB are reported to be influenced by the fibre shape. As a result, this study was conducted to see how sodium hydroxide treatment affected the surface morphology and tensile strength of oil palm empty fruit bunches. Alkaline treatment with sodium Hydroxide is used in compatibility tests (NaOH) where to identified the physical properties for the fibre with different concentration of NaOH. This research finding found out that the higher the concentration, it will reduce the compatibility concerns which include the residual oil, sugar, lignin, hemicellulose and cellulose. Where the finding of mechanical properties with tensile test using different concentration show that the optimum value where on 4% of sodium hydroxide (NaOH). After going through compatibility enhancement procedures, the results suggested that EFB fibre can be considered a suitable substitute material for CFB in non-load bearing applications.